Bahasa Inggris - Krishna Aji; Erwin Ladjinga; Endah Widianti; Tri Mulya Hartati; Gunawan Hartono; Tiara Sarastika; Djoko Mulyanto (Acta Solum, 2026)
The phenomenon of environmental degradation threatens various sectors, including agriculture in coastal ecosystems, thereby weakening the land’s carrying capacity. On the other hand, information about soil resources in fluvial-marine landscapes has formed a complex, unique system that influences geomorpho-pedological characteristics. This study aims to (1) investigate variations in soil morphological characteristics under different agricultural practices and (2) interpret the results of soil genesis processes within the framework of geomorpho-pedological evolution in fluvio-marine landscapes. The research was conducted in Tobo Ino Village, Wasile Subdistrict, Subaim, East Halmahera Regency, North Maluku Province, Indonesia. The methodology used was a stratified sampling method to identify soil profiles based on USDA standards for two different land-use practices. This was followed by laboratory-scale physicochemical analysis of the soil in accordance with the Agricultural Instrument Standardization Agency, Ministry of Agriculture, Indonesia. The results show that land use activities affect soil morphology and classification. Fluvaquentic Endoaquepts soil classification is found in rice paddy field practices, while Typic Eutrudepts is found in mixed plantations. Along with similar geomorphological conditions but different soil evolution processes, this results in different land resource management practices. This approach offers a process-based understanding that is essential for sustainable agricultural planning in dynamic coastal-alluvial landscapes in wet tropical regions to achieve the Sustainable Development Goals (SDGs) and the Eight Goals of the Unitary State of the Republic of Indonesia.